12-15sqrt6 + 8sqrt6 - 10sqrt36'yı nasıl basitleştirirsiniz?

12-15sqrt6 + 8sqrt6 - 10sqrt36'yı nasıl basitleştirirsiniz?
Anonim

Cevap:

# -48-7sqrt (6) #

Açıklama:

# 12-15sqrt (6) + 8sqrt (6) -10sqrt (36) #

# = 12-15sqrt (6) + 8sqrt (6) -10sqrt (6 ^ 2) #

# = 12-15sqrt (6) + 8sqrt (6) -10 * 6 #

# = 12-15sqrt (6) + 8sqrt (6) -60 #

# = 12-60 - (+ 15 + 8) sqrt (6) #

# = - 48-7sqrt (6) #

Cevap:

# -48- (7 * sqrt (6)) #

Açıklama:

12. - (+ 15 * sqrt (6)) + (8 * sqrt (6)) + (- 10 * sqrt (36)) #

Biz biliyoruz ki #sqrt (36) = 6 #.

Yani, 12. (+ - 15sqrt (6)) + (8 * sqrt (6)) + (- 60) #.

#12-60=-48#

Yani, # -48 - (+ 15sqrt (6)) + (8 * sqrt (6)) #

Şimdi çıkar #sqrt (6) # Son iki parantezden.

Bu bize verecek # -48 + (sqrt (6) * (- 15 + 8)) #

#-15+8=-7#

Yani, cevap olurdu # -48- (7 * sqrt (6)) #